2022
DOI: 10.3389/fphy.2022.957025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Branched Fins on Alumina and N-Octadecane Melting Performance Inside Energy Storage System

Abstract: The importance of Phase change material (PCM) energy storage systems is no longer new in the industry. However, the influence of using branched fins inside the energy storage system on the melting process of alumina nanoparticles and n-octadecane has not been reported in the literature. Consequently, the outcome of a study on the numerical simulation for optimizing the melting performance of a PCM in various tubes, including those with branching fins is presented in this report. Four examples were assessed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Subsequently, Kuznetsov and Nield, (2013) revised the model proposed by Buongiorno by considering the passive control of nanoparticles. The revised model of Kuznetsov and Nield was appreciated and used by several researchers, to name a few, Hayat et al (2017), Halim et al (2017), Tripathi et al (2017, Macha et al (2017), Srinivas Reddy and Naikoti, (2016), Vijaya Bhasker Reddy et al (2019), Rauf et al (2019), Giri et al (2017), Kalaivanan et al (2020), Weera et al (2022), Abbasi et al (2021), andAcharya (2021). They concluded that the revised Buongiorno model (RBM) is relevant for studying the heat transport of nano liquids.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Kuznetsov and Nield, (2013) revised the model proposed by Buongiorno by considering the passive control of nanoparticles. The revised model of Kuznetsov and Nield was appreciated and used by several researchers, to name a few, Hayat et al (2017), Halim et al (2017), Tripathi et al (2017, Macha et al (2017), Srinivas Reddy and Naikoti, (2016), Vijaya Bhasker Reddy et al (2019), Rauf et al (2019), Giri et al (2017), Kalaivanan et al (2020), Weera et al (2022), Abbasi et al (2021), andAcharya (2021). They concluded that the revised Buongiorno model (RBM) is relevant for studying the heat transport of nano liquids.…”
Section: Introductionmentioning
confidence: 99%